Manajemen Perubahan dalam Peningkatan Kualitas Widyaiswara - Teguh Anggoro (Badan Pendidikan dan Pelatihan Kementerian Pertahanan, 2024)
This research departs from the problem of the low willingness of the Pusdiklat Bela Negara to change to improve its quality. Their performance demands are to produce students who have an understanding of defending the country and can actualize it and socialize it with others. The argument built in this study is that the quality of widyaiswara in the state defense education and training center has not improved because there is no change in work culture. Thus, the proposition built in this study is,